(untitled) (Eurasian Journal of Ecology, 2016)
The article describes a new mechanism of stimulation of cell division. This hypothesis is based on the geometric (stereometrically) changes in cell volume tensile fabrics. The volume change due to a change in cell shape, it is, in our opinion, leads to stimulation of cell division.